Implementasi Pemasaran Digital untuk Memperluas Jangkauan Pasar Produk Lokal melalui Media Sosial - Ardiansyah Ardiansyah; Sri Wahyuni; Rahma Adauwiyah; Muhammad Ridwan Satria; Febi Fadillah; Teguh Ikhsani Putra (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Indonesian local products face challenges in expanding market reach due to limited digital literacy and suboptimal marketing strategies, despite social media penetration reaching 139 million active users. This study aims to analyze the effective implementation of digital marketing to expand the market reach of local products through social media. The research method uses a qualitative approach with a literature study of scientific publications for the 2021-2025 period from trusted academic databases. The analysis was carried out through content analysis with a thematic approach to identify strategies, challenges, and success factors for digital marketing. The findings of the study show that Instagram and TikTok are identified as effective platforms. One case study within the reviewed literature reports an increase in market reach of up to 340% and revenue growth of 156%, indicating the potential impact of optimized social media marketing when applied contextually. Content strategies that integrate local wisdom, authentic storytelling, and high-quality visuals have been proven to significantly increase brand loyalty. Cultural adaptation in marketing communication is a key factor in success. The main challenges include limited digital literacy (only 23% of MSMEs have a structured strategy), lack of competent human resources, and uneven infrastructure. The conclusion of the study confirms that digital marketing optimization requires a holistic approach including continuous training, integrated multi-platform strategies, and the utilization of data analytics to increase the competitiveness of local products in the digital era.